Sobre la explicación teleológica en Aristóteles - Furlan, Timothy J. (Sapientia, 2018)
In a well-known passage at the beginning of NE I. 7 Aristotle concludes that eudaimonia must be that supreme good (to ariston) toward which all our actions aim. Although, he admits, this conclusion is generally agreed upon —it is, in other words, accounted for by the opinions of the many and the wise1— nevertheless a more explicit account is required. In her early work on Aristotle’s De Motu Animalium, Martha Nussbaum expresses puzzlement about this passage and makes a fascinating and provocative suggestion, namely, that Aristotle’s use of function argumentation here differs from its usual deployment throughout his biological and zoological works.